DIVERSITY OF CELLULASE ACTIVE MICROMYCETES IN THE ANT-HILL SOIL ENVIRONMENT OF PARKS AND GARDENS OF JAMMU CITY (INDIA) - VISHAL SHARMA; GEETA SUMBALI (International Journal of Pharma and Bio Sciences, 2013)
One hundred and twenty soil samples collected from ant-hills of various parks and gardens of Jammu City (India) were screened for the cellulase active micromycetes. In all, forty species belonging to sixteen fungal genera were recovered from the samples by using dilution plate method. In the present study, Congo red test was performed for detecting the cellulase active micromycetes and twenty seven fungal species were detected to be positive. Quantification of cellulase activity of the positive fungal species was done by using dinitrosalicylic acid (DNSA) method and eight of them, namely Trichoderma viride, T. harzianum, Penicillium chrysogenum, P. griseofulvum, Trichothecium roseum, Aspergillus niger, Fusarium pallidoroseum and Acremonium implicatum were discovered to be highly cellulolytic in comparison to other positive micromycetes. Their cellulase activity ranged from 0.42 to 0.76 µmol/ml/min. Maximum cellulase activity was shown by T. viride.